2021
DOI: 10.1111/jhn.12845
|View full text |Cite
|
Sign up to set email alerts
|

Registered dietitians' perceptions and use of the plant‐based recommendations in the 2019 Canada's Food Guide

Abstract: Background In 2019, Canada's Food Guide underwent its first transformation in over a decade. The change received considerable attention given the increased focus on plant‐based proteins and the decision to eliminate the milk and alternatives food group. Yet little is known about health professionals' views of these updates. In response, the present study examined Canadian dietitians' attitudes and behaviours towards the guide's expanded plant‐based recommendations. Methods A pan‐Canadian cross‐sectional online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Most included studies were quantitative [14][15][16][17][18][19][20][21][22] . The only one with a qualitative-quantitative approach was McHugh et al 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most included studies were quantitative [14][15][16][17][18][19][20][21][22] . The only one with a qualitative-quantitative approach was McHugh et al 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Three articles [20][21][22] included nutritionists or dietitians in the sample, and they have three different designs. Asher et al 20 analyzed dietitians' perspectives regarding the new Canadian guideline, which includes more open recommendations on plant-based protein alternatives. Here, the professionals seemed to have appreciated the change and implemented the new recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…Interest in plant-based diets as a therapeutic option for CKD continues to grow globally, and recent studies have explored dietitians [ 41 , 42 ] and nephrology professionals’ [ 43 ] perceptions of plant-based eating. However, to our knowledge, this is the first study to provide explicit information on what might be required in practice to implement plant-based diets and strategies dietitians could use to support their patients with CKD to consume more plant foods.…”
Section: Relevance To Practicementioning
confidence: 99%
“…The release of the CFG-2019 elicited positive reactions (8, 9), but also raised concerns on nutrient adequacy. For example, preliminary modeling of eating patterns consistent with the CFG-2019 plate snapshot revealed that adherence may be insufficient to meet calcium and vitamin D requirements (10).…”
Section: Introductionmentioning
confidence: 99%